Spontaneous Echo Contrast at a Large Inter‐Atrial Septal Aneurysm. Issue 9 (6th June 2013) - Pratap, Pravin; Foster, Mariah M.; Labovitz, Arthur J.; Chae, Sanders H.
Mini‐Abstract A 75‐year‐old woman presented with typical atrial flutter. Prior to ablation, a transesophageal echocardiogram demonstrated significant spontaneous echo contrast (SEC) at the site of a large inter‐Atrial septal aneurysm (ASA). After ablation of the arrhythmia, recovery of her left ventricular function, and 3 months of therapeutic anticoagulation with warfarin, she continued to have significant SEC at the site of her ASA, implicating the ASA as the source for the SEC.